Borrelia burgdorferi Surface Exposed GroEL Is a Multifunctional Protein - Thomas Cafiero; Alvaro Toledo (Pathogens, 2021)
The spirochete, Borrelia burgdorferi, has a large number of membrane proteins involved in a complex life cycle, that includes a tick vector and a vertebrate host. Some of these proteins also serve different roles in infection and dissemination of the spirochete in the mammalian host. In this spirochete, a number of proteins have been associated with binding to plasminogen or components of the extracellular matrix, which is important for tissue colonization and dissemination. GroEL is a cytoplasmic chaperone protein that has previously been associated with the outer membrane of Borrelia. A His-tag purified B. burgdorferi GroEL was used to generate a polyclonal rabbit antibody showing that GroEL also localizes in the outer membrane and is surface exposed. GroEL binds plasminogen in a lysine dependent manner. GroEL may be part of the protein repertoire that Borrelia successfully uses to establish infection and disseminate in the host. Importantly, this chaperone is readily recognized by sera from experimentally infected mice and rabbits. In summary, GroEL is an immunogenic protein that in addition to its chaperon role it may contribute to pathogenesis of the spirochete by binding to plasminogen and components of the extra cellular matrix.